Spar : poems - Volkman, Karen (Iowa poetry prize., 2002)
Karen Volkman's award-winning collection Spar has as its central form a highly compressed, musical variant of the prose poem. Volkman develops a new lyric density that marries the immediacy of image-centered poetry to the rhythmic resources of prose. Her first poem begins, "Someone was searching for a Form of Fire," and this wild urge to seek form--and thus definition--in the most uncontainable of elements propels the book forward; each poem maps the mind's evolving positions in response to its variable and perilous encounters